Little Gamelan Art Learning Model to Grow Pancasila Values in Kindergarten Students - Pamungkas, Joko; Harun, Harun; Cahya Rahmawati, Septika; Lathifah, Wildiani; Anggraeni, Putri (Green Publisher Indonesia, 2022)
This study aims to: (1) determine the prototype of the little gamelan art learning model for inculcating Pancasila values ​​in kindergarten children, (2) determine the feasibility and practicality of the little gamelan art learning model (3) determine the effectiveness of the little gamelan art learning model (4) knowing the process of growing Pancasila values ​​in kindergarten children while playing a little gamelan art. The subjects of the study were group B kindergarten children, kindergarten leaders, and kindergarten educators in the Special Region of Yogyakarta. Need assessment data collection is done through interviews, list of documents, and questionnaires. The results of this study indicate that the assessors of the validity of gamelan experts and children's learning are met according to criteria 0.9 in the Validity Coefficient Table with an error rate of 5%. Likewise, the reliability between raters with the test-retest method obtained a consistency score according to the criteria in the Reliability Table with an error rate of 5%. The effectiveness of the little gamelan in stimulating Pancasila for early childhood is very significant. This is based on a one-sample t-test that the acceptance of the alternative hypothesis and the rejection of the null hypothesis is that the children's Pancasila achievement during and after playing the gamelan exceeds the Pancasila scores achieved by most of the PAUD teachers involved in this study. The values ​​that are stimulated in playing the little gamelan are praying, knowing God's creation, being grateful, appreciating, polite, appreciating, compact, harmonious, deliberation, leadership, fair, taking turns.